Fabrication of Namib Beetle Inspired Biomimetic Amphi-phobic Surfaces Using Adsorbed Water as a Monomer. (2016) - Oyola-Reynoso, Stephanie; Tevis, Ian; Chen, Jiahao; Bloch, Jean Francis; Thuo, Martin
Abstract: Chemical grafting of small molecule reagents onto polymeric fibrous materials, like paper, has been used to modify their wetting properties. Several reagents like trichlorosilanes, which can react with water or hydroxyls, have been used with the expectation that a monolayer, single molecule or polymerized single-molecule layer, is formed on the paper fiber surface. Presence of adsorbed water, however, would complicate the formation of a monolayer, especially in case of polyvalent reagents. We hypothesized that adsorbed water is a good co-monomer for polyvalent water-reactive reagents, therefore chemical grafting with polyvalent molecules would give polymeric gels instead of a monolayer. Reaction of trivalent reagents with paper in vacuo leads to formation of polymeric gels. By optimizing surface energy mismatch, through felicitous choice of chemical moieties on the monomer, self-assembly leads to formation of nano- to micro particles on the surface of paper fibers. We observe that, as expected, the wetting properties correlate well with the size and distribution of particles. We conclude that the recently reported ultra-hydrophobicity of chemically modified paper is not only due to inherent roughness of the paper fibers, but also due to a secondary roughness introduced by surface polymerization. Using this technique, we prepared amphi-phobic biomimetic surfaces inspired by the namib beetle. This talk will also address potential utility of such surfaces.